Front Matter - Durelli, Rafael; Rocha, Lincoln (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM); 2020: Anais do VIII Workshop de Visualização, Evolução e Manutenção de Software, 2020)
The 8th Workshop on Software Visualization, Evolution, and Maintenance (VEM 2020) is part of the 11th Brazilian Congress on Software: Theory and Practice (CBSoft 2020), held in virtual mode on October 19, 2020. Its main goal is to foster the integration of the software visualization, evolution and maintenance communities, providing a Brazilian forum where researchers, students, and professionals can present their work and exchange ideas on the principles, practices, and innovations related to their respective areas of interest. The VEM 2020 Program Committee (PC) is composed of 44 active researchers in the areas of software visualization, evolution, and maintenance, who come from several regions of Brazil. The PC members selected eight interesting and promising papers to be presented at VEM 2020 from a total of 12 submissions. Each submission was evaluated by at least three PC members based on their originality, technical quality, and adequacy to the event’s scope.